Multi-Input Power Converter for Renewable Energy System using Active Current Sharing Scheme - Mazelan, Fahim Nabil (2018)
In this paper, a multi-input power converter (MIPC) dedicated for renewable energy system (RES) using active current sharing scheme is proposed. The relevancy of this project is in recent times, conventional energy such fossil fuels are depleting. Due to this limited energy source, a rise in interest on renewable energy system (RES) as a potential replacement has happened. To do so, proper technologies are needed to tap into RES capabilities. Currently, technology such as conventional MIPC offer multi input power conversion with the same voltage and current. This is however not suitable for RES due to its continuous varying output characteristic. Hence, the proposed MIPC aim to overcome this problem. This MIPC consists of a multi- input parallel DC-DC converter which offer the ability to produce a regulated output from several renewable energy system and active current sharing schemes, a feedback loop to control the load sharing in way that is equal among all paralleled converter. The renewable energy focus on this research is photovoltaic and fuel cells. This idea proposes a power converter which can receive multiple RES input with variable voltage level and convert it to produce a stable regulated output. This paper will mainly aim on design, simulate and analyse the MIPC which employs an averaged current sharing mode as its active current sharing error signalling processing control strategy. To obtain the result, the proposed MIPC will be simulated under several specific input condition known as Case via Simulink. Each Case will have its own different input value. This Case condition will act as the varying characteristic of RES. In terms of analysing the result, a conventional MIPC with pulse generator is simulated under the same Case condition and compared to the proposed MIPC results. The result will indicate that the proposed MIPC shows consistent regulated output throughout each Case while the conventional MIPC shows variable regulate output value, each time different Case condition is simulated. Hence, when seeing it from RES point if view, the conventional MIPC will yield an unstable output when the input RES started to vary. In comparison to the proposed MIPC, the output will remain constant even though the RES input changes over time.